QUR’AN IN DAILY LIFE: Studi Visualisasi Mushaf Al-Qur’an di Era Post-Modernisme - Rohimatus Sholihah; Fathurrosyid; Abd. Basid (Jurnal Studi Qur'an dan Tafsir, 2024)
One of Quran's privileges is that reading it is worship. Basically, all of worships which is recommended by religion have process of closing to Allah. Reading al-Qur'an also have certain manners. One of them is ablution, reading it in holy and clean place, reading it slowly and humblely. Qur'an in daily life is one of Muslim's effort to unifies Quranic values with postmodern society life. By Qur'an in daily life, postmodern Muslim is expected to be able reading the Qur'an easily. Therefore, visualization of mushaf is needed which is developed and its form, style and composition are alluring. So that al-Qur'an is printed as interesting forms as possible and accessible whenever and wherever. But, all the convenience obtained cause Muslims not to take care manners of reading the Qur'an so that it is read in carelessly places. Finally, virtue value of reading the Qur'an is not obtained. Using visualization of mushaf theory, this research intends to reveal two things. First, what is meant by Qur'an in daily life? Second, how is practice of Qur'an in daily life according to comentators? This research produces two conclusion. First, Qur'an in daily life is a concept which move on from assumption that Quran is positioned as source of Muslims life, so that presumed there is interaction between Quran and them. Second, there are certain manners of reading the Quran which refer to Quranic verses, for example QS. An-Nahl [16]: 98, QS. Al-Muzzammil [73]: 4, and QS. Shaad [38]: 29. Reading ta'awwuż, when someone will read Qur'an, reading it slowly and reading it by reflecting its meaning (tadabbur).